Venture Capital Financing as A Driver for Entrepreneurship Development in Africa. A Literature Review and Future Research Agenda - Kato Idi Ahmed Idi; Chiloane -Tsoka Evelyn Germinah, Prof (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: Several academics and practitioners have observed entrepreneurship development as a critical pillar for the prosperity of high-growth entrepreneurial ventures, new job opportunities, promotion of exports, and improvement of tax revenue across all countries. However, little is known about the role of VC in stimulating entrepreneurship development in Southern and East African regions.